1998
DOI: 10.1073/pnas.95.13.7556
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of an interferon γ-dependent tumor surveillance system in immunocompetent mice

Abstract: This study demonstrates that endogenously produced interferon ␥ (IFN-␥) forms the basis of a tumor surveillance system that controls development of both chemically induced and spontaneously arising tumors in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
955
4
15

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,290 publications
(1,054 citation statements)
references
References 31 publications
47
955
4
15
Order By: Relevance
“…However, analysis of chemical carcinogenesis in Stat1-mutant and IFNg receptor-mutant animals revealed the existence of an IFNg-mediated tumor surveillance system that operates in immunocompetent animals (Kaplan et al, 1998). This study demonstrated that endogenously produced IFNg was required for a tumor surveillance system capable of controlling development of both chemically induced and spontaneously arising tumors.…”
Section: Stat1 Growth Control and Cancermentioning
confidence: 75%
“…However, analysis of chemical carcinogenesis in Stat1-mutant and IFNg receptor-mutant animals revealed the existence of an IFNg-mediated tumor surveillance system that operates in immunocompetent animals (Kaplan et al, 1998). This study demonstrated that endogenously produced IFNg was required for a tumor surveillance system capable of controlling development of both chemically induced and spontaneously arising tumors.…”
Section: Stat1 Growth Control and Cancermentioning
confidence: 75%
“…Irrespective of the stimulus used, we failed to detect any differences. As p185 bcr/abl -transformed cells respond with apoptosis to interferon treatment (Grawunder et al, 1993) and interferon-g is a key factor in tumor surveillance, we tested survival in the presence of interferon-g (IFN-g; Kaplan et al, 1998;Shankaran et al, 2001 Figure 2c). Finally, the expression of bcl 2 , bcl x and bax was reasonably similar in these cell lines as was the expression of c-Jun and c-Fos, and the upstream kinases JNK1 and JNK2 ( Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Although Stat1-deficient mice do not display a heightened incidence of spontaneous neoplasms, they are more sensitive to chemical induction of tumors (Kaplan et al, 1998;Levy and Gilliland, 2000). However, STAT1 expression is frequently upregulated in tumors (Frank et al, 1997;Spiekermann et al, 2001;Widschwendter et al, 2002;Benekli et al, 2003;Hudelist et al, 2005) and associated with prosurvival functions under conditions of growth stress, such as X-irradiation (Khodarev et al, 2004), or anticancer therapy (Friedberg et al, 2004;Roberts et al, 2005).…”
Section: Stat1 Is a Prosurvival Factor In Wilms' Tumormentioning
confidence: 99%
“…We observed serine-phosphorylated STAT1 in the developing rat kidney, and it may have a role in kidney development, for example, to promote progenitor cell survival before tissue vascularization. Although STAT1-deficient mice or mice expressing constitutively inactive STAT1-S727A mutant do not have a kidney phenotype (Kaplan et al, 1998;Varinou et al, 2003), probably because activated STAT3 can replace STAT1 to drive the transcription of certain genes (Qing and Stark, 2004), it may be more revealing to evaluate the renal response to overexpression of constitutively active STAT1 during metanephric differentiation or carcinogenesis.…”
Section: Stat1 Is a Prosurvival Factor In Wilms' Tumormentioning
confidence: 99%